Spatial and temporal pattern of soil pH and Eh and their impact on solute iron content in a wetland (Transdanubia, Hungary) - Szalai, Zoltán (Acta Geographica Debrecina Landscape & Environment series, 2008)
Land mosaics have direct and indirect influence on chemical reaction and redox condition of soils. The present paper deals with the relationship between some environmental factors (such as soil and vegetation patterns, micro-relief, water regime, temperature and incident solar radiation) and the pH, Eh of soils and solute iron in a headwater wetland in Transdanubia, Hungary. Measurements have been taken in four different patches and along their boundaries: sedge (Carex vulpina, Carex riparia, three patches and two species), horsetail (Equisetum arvense), common nettle (Urtica dioica). The spatial pattern of the studied parameters are influenced by the water regime, micro-topography, climatic conditions and by direct and indirect effects of vegetation. The indirect effect can be the shading, which has influence on soil temperature and on the incident solar radiation (PAR). Root respiration and excretion of organic acids appear as direct effects.. There have been measured individual pH and Eh characteristic in the studied patches. Soil Eh, pH and solute iron have shown seasonal dynamics. Higher redox potentials (increasingly oxidative conditions) and higher pH values were measured between late autumn and early spring. The increasing physiological activity of plants causes lower pH and Eh and it leads to higher spatial differences. Although temperature is an essential determining factor for Eh and pH, but our results suggest it rather has indirect effects through plants on wetlands.